69.6k views
22 votes
Y= 4x + 1

y= 2x - 5



When using the method called substitution, the best first step in solving the system of equations (shown above) is to:



Set the equations equal to each other since both are y =

Rewrite each equation in the form x =

Multiply all terms in both equations by 2

Add the two equations together

User Oct
by
5.0k points

2 Answers

10 votes
Answer

y=2x + 4

4x - 2x and or 1 - (-5)
User BrianHT
by
6.0k points
7 votes

Answer:

y = 2x + 4

4x - 2x and 1 - (-5) :)

User Desorder
by
4.3k points